2003
DOI: 10.1023/b:ejep.0000040527.59987.b2
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the French Armed Forces

Abstract: Several states, of whom France, have been alarmed about suicide in the military. An observational longitudinal cohort study was conducted to check whether the suicide risk in the French army was higher than in the general population and to find out the more prone to self-harm destruction personnel categories. From 1997 to 2000 inclusive, 230 suicides occurred among 315,934 person.years; i.e., the overall annual crude suicide rate was 18.2 per 100,000 active-duty personnel. With the National data for 1999 as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…However, these studies would not have been able to identify all suicides among UK Armed Forces personnel and did not examine Service or age-specific data. Other nations have made similar comparisons and these studies have also shown lower rates of suicide in the military compared with the general population, with increased rates among young military men 19 20…”
Section: Discussionmentioning
confidence: 73%
“…However, these studies would not have been able to identify all suicides among UK Armed Forces personnel and did not examine Service or age-specific data. Other nations have made similar comparisons and these studies have also shown lower rates of suicide in the military compared with the general population, with increased rates among young military men 19 20…”
Section: Discussionmentioning
confidence: 73%
“…2 This finding has been corroborated in several military samples [3][4][5] ; however, other studies have demonstrated conflicting results. [6][7][8][9][10] To date, it is unclear whether military personnel have an increased or decreased risk of suicidal behaviour.…”
mentioning
confidence: 99%
“…After years of a decreasing suicide rate in the US military, levels similar to the 1990s were reached again (Helmkamp, ). Until the 1990s, military suicide rates were considerably higher than today in Europe as well (Desjeux, Labarère, Galoisy‐Guibal, & Ecochard, ; Street et al., ).…”
mentioning
confidence: 99%
“…So due to discussions about rising suicide rates, a huge number of registry studies on risk group analyzes have been conducted in the US. Many studies have identified male gender as a suicide risk factor in its own right (Armed Forces Health Surveillance Center, AFHSC, ; Bell, Harford, Amoroso, Hollander, & Kay, ; Desjeux et al., ; Helmkamp, ; Hyman, Ireland, Frost, & Cottrell, ; Kapur, While, Blatchley, Bray, & Harrison, ; Kessler, Stein, et al., ; Kessler, Warner, et al., ; LeardMann et al., ; Martin et al., ; Miller et al., ; Scoville, Gubata, Potter, White, & Pearse, ; Street et al., ; Thoresen & Mehlum, ). These gender‐specific effects are also known in hospitalized German military samples (Willmund et al., ; Zimmermann et al., )).…”
mentioning
confidence: 99%
See 1 more Smart Citation